Clinical Information System Using Extreme Programming Method - Purnama, Iwan (Publisher Cv. Inara, 2023)
Clinic is a health service facility that organizes individual health services and provides basic and/or specialist medical services. If the clinic does not use a computerized system, it will hamper the patient handling process. Obstacles were found at the Rantauprapat Internal Clinic Clinic, including patient registration which was still done manually with patients having to fill out paper forms directly to the clinic, not having a queuing system for treatment, medical record management which was still manual by handwriting. This can take a lot of time in the data search process. The purpose of this application is to facilitate daily operational activities in clinics that run quickly and precisely, as well as medical data management to be more accurate (minimizing human error). The analysis method uses the Soft System Methodology (SSM), and the system development method uses Extreme Programming (XP). This website-based application uses the PHP programming language which is supported by the MySQL database. Based on blackbox testing, all features can run/100% valid. This information system helps the work process in the clinic to be faster, documenting structured medical records, reducing paper use, and facilitating activities in patient care.